2014
DOI: 10.1001/jamaoto.2014.267
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hearing Aids on the Speech and Language Development of Children With Hearing Loss

Abstract: Importance Hearing loss (HL) in children can be deleterious to their speech and language development. The standard of practice has been early provision of hearing aids (HAs) to moderate these effects; however, there have been few empirical studies evaluating the effectiveness of this practice on speech and language development among children with mild-to-severe HL. Objective To investigate the contributions of aided hearing and duration of HA use to speech and language outcomes in children with mild-to-sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
153
2
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(171 citation statements)
references
References 21 publications
4
153
2
12
Order By: Relevance
“…Less consistent HA use may not appear to be a cause for alarm because children with mild HL have significant residual hearing and some access to the speech spectrum even when unaided. On the other hand, evidence suggests that children with mild HL show as much benefit from HAs as children with moderateto-severe HL on measures of articulation and language (Tomblin, Oleson, Ambrose, Walker, & Moeller, 2014). Further research has shown that daily HA use influences language outcomes in early school-age children with mild HL, particularly for morphosyntactic acquisition (Walker, Holte, et al, 2015).…”
Section: Parental Attitudes Toward Intervention and Amplificationmentioning
confidence: 99%
“…Less consistent HA use may not appear to be a cause for alarm because children with mild HL have significant residual hearing and some access to the speech spectrum even when unaided. On the other hand, evidence suggests that children with mild HL show as much benefit from HAs as children with moderateto-severe HL on measures of articulation and language (Tomblin, Oleson, Ambrose, Walker, & Moeller, 2014). Further research has shown that daily HA use influences language outcomes in early school-age children with mild HL, particularly for morphosyntactic acquisition (Walker, Holte, et al, 2015).…”
Section: Parental Attitudes Toward Intervention and Amplificationmentioning
confidence: 99%
“…13 Intervention during this "critical" or "sensitive" period of rapid brain growth is characterized by neurogenesis, axonal and dendritic proliferation, synaptogenesis, cell apoptosis, synaptic pruning, and myelination with gliogenesis, and is often associated with the best possible outcomes. 1,13 In fact, several studies have demonstrated that early detection of hearing loss through newborn or neonatal hearing screening (NHS) programs accompanied by timely provision of hearing devices by the first year of life is associated with significant developmental outcomes and substantial cost savings, [15][16][17][18][19][20][21][22] although robust studies on the long-term economic benefits are still needed. 23 Other benefits of EHDI are summarized in Table 1.…”
Section: Table 1 Benefits Of Early Detection Of Hearing Impairment Thmentioning
confidence: 99%
“…Para minimizar os efeitos negativos da perda auditiva é essencial o uso de recursos tecnológicos, como próteses auditivas e implante coclear, que possibilitem a reabilitação auditiva da criança em fase inicial do desenvolvimento e aquisição da linguagem 1 . Os primeiros anos de vida das crianças com deficiência auditiva ou surdez são essenciais para o desenvolvimento da linguagem e audição.…”
Section: Introductionunclassified